Work-life balance and the economic crisis. some insights from the perspective of comparative law - Mella Méndez, Lourdes; Serrani, Lavinia (ADAPT labour studies book-series., 2015)
No one can deny the significance attributed to the issue of reconciling work and private life by contemporary society, the EU and other international organisations. Its relevance is evident in the multifaceted nature of this topic and the need for each party to the employment contract to strike a proper balance between professional and personal responsibilities, based on the assumption that people can successfully harmonise their work with life. Following on from these considerations, this volume provides a detailed analysis of work-life balance and its regulation in a number of EU countries, emphasizing the consequences that the current economic crisis has brought about in this field.--